AtSERPIN1 is an inhibitor of the metacaspase AtMC1‐mediated cell death and autocatalytic processing in planta. Issue 3 (3rd February 2017) - Lema Asqui, Saul; Vercammen, Dominique; Serrano, Irene; Valls, Marc; Rivas, Susana; Van Breusegem, Frank; Conlon, Frank L.; Dangl, Jeffery L.; Coll, Núria S.
Summary: The hypersensitive response (HR) is a localized programmed cell death phenomenon that occurs in response to pathogen recognition at the site of attempted invasion. Despite more than a century of research on HR, little is known about how it is so tightly regulated and how it can be contained spatially to a few cells. AtMC1 is an Arabidopsis thaliana plant metacaspase that positively regulates the HR. Here, we used an unbiased approach to identify new AtMC1 regulators. Immunoaffinity purification of AtMC1‐containing complexes led us to the identification of the protease inhibitor AtSerpin1. Our data clearly showed that coimmunoprecipitation between AtMC1 and AtSerpin1 and formation of a complex between them was lost upon mutation of the AtMC1 catalytic site, and that the AtMC1 prodomain was not required for the interaction. AtSerpin1 blocked AtMC1 self‐processing and inhibited AtMC1‐mediated cell death. Our results constitute an in vivo example of a Serpin acting as a suicide inhibitor in plants, reminiscent of the activity of animal or viral serpins on immune/cell death regulators, including caspase‐1. These results indicate a conserved function of a protease inhibitor on cell death regulators from different kingdoms with unrelated modes of action (i.e. caspases vs metacaspases). Abstract : See also the Commentary on this article byvan der Hoorn & Rivas, 218 : 879–881 .